Citizen engagement initiatives in precision health in the European Union member states: a scoping review. Issue 7 (9th July 2021) - Pezzullo, Angelo Maria; Sassano, Michele; Hoxhaj, Ilda; Pastorino, Roberta; Boccia, Stefania
Abstract : Introduction: Precision health requires citizens that are empowered to orient health decisions towards their personal values, aware of the benefits and risks, and committed to sharing their personal data to trustful institutions. Effective citizen engagement initiatives are fundamental for the success of a precision health approach. Objective: To provide an overview of citizen engagement initiatives in precision health in European Union (EU) member states. Design: Scoping review. Methods: The electronic databases PubMed, Web of Science, CINAHL and Embase were searched to include articles published in English. Furthermore, desk research was conducted in English, Dutch, French, Italian and Spanish. Articles or reports regarding ongoing initiatives of citizen engagement in precision health conducted in EU member states and published from January 2015 to July 2020 were considered eligible. A quality assessment of the retrieved entries using Critical Appraisal Skills Programme tool was conducted. Results: We identified nine documents, which reported eight ongoing citizen engagement initiatives, with substantial variability. Government agencies, non-governmental organisations and scientific societies were the main organisers and funders. Most of the initiatives were conducted in the UK. Genomics was the most emphasised aspect of precision health in these initiatives. Among the identified initiatives, both in-person and digital means were reported. Conclusion: Our work provides an overview of current citizen engagement initiatives in the EU that can be useful for stakeholders interested in designing and developing precision health projects enriched by meaningful citizen participation. PROSPERO registration number: CRD42020193866.